The regulation of electro-optical properties of the polymer dispersed liquid crystal films doped ZnO whiskers under applied pre-orientation voltage. Issue 14 (14th November 2022) - He, Zemin; Li, Jinqian; Zhang, Wenfang; Gao, Jianjing; Ma, Cheng; Yao, Ruijuan; Yao, Xinlin; Miao, Zongcheng; Wang, Dong
ABSTRACT: This study demonstrates a simple and effective method for the fabrication of PDLC films with low driving voltage by applying a pre-orientation voltage during the photoinitiated polymerisation process. The results indicated that the electro-optical performances of PDLC films have been regulated successfully with the pre-orientation voltage method, in which the voltage could pre-orient the LC molecules and change the interface between the LC molecules and the polymer matrix. By manipulating the proportion of liquid crystal and polymer monomers and introducing ZnO whiskers as the dopant, the driving voltage was dramatically reduced and the sample could be fully driven by an electric field with a voltage of 32 V below the safe voltage. The results indicated that the polymer meshes were broadened by the addition of ZnO whiskers due to their excellent UV-absorbing properties that result in a slower polymerisation rate, while the contrast ratio could maintain a good value of 31. It has been found that both application of pre-orientation voltage and doped ZnO whiskers can optimise the electro-optical performance of the PDLC and reduce the driving voltage. Therefore, this experiment is expected to provide certain research value to fabricate the low-driven PDLC films for practical applications. GRAPHICAL ABSTRACT: uf0001